Frequency of rare BCR‐ABL1 fusion transcripts in chronic myeloid leukemia patients. (29th December 2016) - Arun, A. K.; Senthamizhselvi, A.; Mani, S.; Vinodhini, K.; Janet, N. B.; Lakshmi, K. M.; Abraham, A.; George, B.; Srivastava, A.; Srivastava, V. M.; Mathews, V.; Balasubramanian, P.
Summary: Introduction: The hallmark of chronic myeloid leukemia (CML) is the presence of Philadelphia chromosome, its resultant fusion transcript ( BCR‐ABL1 ), and fusion protein (p210). Alternate breakpoints in BCR (m‐bcr, μ‐bcr, and others) or ABL1 result in the expression of few rare fusion transcripts (e19a2, e1a2, e13a3, e14a3) and fusion proteins (p190, p200, p225) whose exact clinical significance remains to be determined. Methods: Our study was designed to determine the type and frequency of BCR‐ABL1 fusion transcripts in 1260 CML patients and to analyze the prognosis and treatment response in patients harboring rare BCR‐ABL1 fusion transcripts. Results: The frequency of various BCR‐ABL1 fusion transcripts was as follows: e14a2 (60%), e13a2 (34.3%), e1a2 (1.2%), e1a2 + e13a2 (2.0%), e1a2 + e14a2 (1.8%), e19a2 (0.3%), and e14a3 (0.3%). CML patients with e1a2 transcripts had higher rates of disease progression, resistance, or suboptimal response to imatinib and failed to achieve major molecular response. Conclusion: Characterization of the specific fusion transcript in CML patients is important owing to the difference in prognosis and response to therapy in addition to the conventional need for monitoring treatment response. CML patients with e1a2 transcripts have to be closely monitored due to the high incidence of disease progression and treatment resistance/failure.